ANALISIS YURIDIS DAN DAMPAK KESEHATAN HUKUMAN PIDANA TERHADAP PENYALAHGUNAAN NARKOTIKA DI INDONESIA: KAJIAN KOMPREHENSIF ATAS UNDANG-UNDANG NOMOR 35 TAHUN 2009 DAN UPAYA REHABILITASI DALAM SISTEM PERADILAN PIDANA - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (ADMIN: Jurnal Administrasi Negara, 2025)
The legal analysis and health impact of criminal penalties for drug abuse in Indonesia are crucial issues in efforts to combat drugs effectively and fairly. This study examines the implementation of Law No. 35 of 2009, which regulates a dual system of criminal sanctions and rehabilitation for drug abusers. The results of the study show that although the law has regulated rehabilitation as an alternative, the application of prison sentences is still dominant and often ignores the difference between users and dealers. The health impact of criminal punishment in the form of significant physical and psychological disorders creates an urgent need to strengthen rehabilitation as a recovery effort. Rehabilitation has been proven to be more effective in reducing recidivism and improving the quality of life of abusers compared to prison sentences. The study emphasises the importance of reforming legal policies and the judicial system by integrating health aspects to balance legal protection and the social recovery of drug abusers.